ANALISIS DAMPAK PENGANGGURAN TERHADAP KEMISKINAN DI DKI JAKARTA - Darma Rika Swaramarinda (Faculty of Economics, State University of Jakarta., 2014)
This article was aimed at describing connections between unemployment to poverty in DKI Jakarta. In this article, the analysis use descriptive-qualitative. This analysis described in descriptive about unemployment and poverty in DKI Jakarta. Unemployment that occured in DKI Jakarta making poverty is increasing and that seen everywhere. The increase of unemployment in development countries emerging due to the slow growth of employment than the the rapid growth of labor force. Policies need to be created by the local government that can increase the demand of unskilled labor in order to facilitate poor peoples sell their labor and reduce the number of unemployment.